2013
DOI: 10.1371/journal.pone.0054618
|View full text |Cite
|
Sign up to set email alerts
|

Uncaria tomentosa Exerts Extensive Anti-Neoplastic Effects against the Walker-256 Tumour by Modulating Oxidative Stress and Not by Alkaloid Activity

Abstract: This study aimed to compare the anti-neoplastic effects of an Uncaria tomentosa (UT) brute hydroethanolic (BHE) extract with those of two fractions derived from it. These fractions are choroformic (CHCl3) and n-butanolic (BuOH), rich in pentacyclic oxindole alkaloids (POA) and antioxidant substances, respectively. The cancer model was the subcutaneous inoculation of Walker-256 tumour cells in the pelvic limb of male Wistar rat. Subsequently to the inoculation, gavage with BHE extract (50 mg.kg−1) or its fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 54 publications
1
20
0
3
Order By: Relevance
“…Among Uncaria species, U. tomentosa was considered as effective antitumor candidate to inhibit cancer cells growth, such as HL-60 (leukemia) (Cheng et al, 2007;Bacher et al, 2006), MCF7 and MT-3 (breast) (Riva et al, 2001;Sun et al, 2012a;Pilarski et al, 2010;García Giménez et al, 2010), (Dreifuss et al, 2013) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Xian et al, 2014Xian et al, et al, 2007. The correlations between pharmacological properties of U. tomentosa and active compounds revealed that oxindole alkaloids and triterpenes are major bioactive constituents.…”
Section: Anticancer Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among Uncaria species, U. tomentosa was considered as effective antitumor candidate to inhibit cancer cells growth, such as HL-60 (leukemia) (Cheng et al, 2007;Bacher et al, 2006), MCF7 and MT-3 (breast) (Riva et al, 2001;Sun et al, 2012a;Pilarski et al, 2010;García Giménez et al, 2010), (Dreifuss et al, 2013) 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Xian et al, 2014Xian et al, et al, 2007. The correlations between pharmacological properties of U. tomentosa and active compounds revealed that oxindole alkaloids and triterpenes are major bioactive constituents.…”
Section: Anticancer Activitiesmentioning
confidence: 99%
“…The sole substances responsible for its anti-neoplastic effect was a synergic combination of substances based on antioxidant activity rather than just oxindole alkaloids (Coussens and Werb, 2002;Mantovani et al, 2008;Dreifuss et al, 2013).…”
Section: Anticancer Activitiesmentioning
confidence: 99%
“…In addition to the ethnopharmacological data, various pharmacological tests performed in vitro and in vivo confirmed its antioxidant ( DREIFUSS et al, 2013), anticancer (PILARSKI et al, 2010, anti inflammatory (ROJAS-DURAN et al, 2012), antimicrobial (CCAHUANA-VASQUEZ et al, 2007, antiherpetic (CAON et al, 2014), contraceptive (NOGUEIRA NETO et al, 2011), neuroprotective (SHI et al, 2013), and antidiabetic (DOMINGUES et al, 2011) activities.…”
Section: Developmentmentioning
confidence: 90%
“…Cat's claw contains several active compositions including ajmalicine, campesterol, carboxyl alkyl esters, akuammigine, sitosterols, rutin, chlorogenic acid, speciophylline, catechin, cinchonain [15], corynoxeine, harman, daucosterol, epicatechin, hirsuteine, corynantheine, hirsutine, loganic acid, mitraphylline, iso-pteropodine, oleanolic acid, ursolic acid, lyaloside [16], rhynchophylline, palmitoleic acid, pteropodine quinovic acid glycosides, procyanidins [10], stigmasterol, 3,4-dehydro-5-carboxystrictosidine, vaccenic acid, uncarine A thru F, and strictosidines [10,17]. Moreover, other reports revealed that various compounds other than oxindole alkaloids such as rotundifoline and isorotundifolune, coumarins, flavonoids, quinovic acid glycosides, and triterpenes may be responsible for the cat's claw medicinal effects [18,19].…”
Section: Chemical Constituents Of U Tomentosamentioning
confidence: 98%